Development 0f A Micro:Bit-Based STEM Biology Module on The Human Circulatory System With Sel to Enhance Digital Literacy and Creativity - Eka Wulandari; Didit Ardianto; Dadang Jaenudin (UIN Fatmawati Sukarno Bengkulu, 2026)
This Research and Development study developed a Micro:bit-based STEM Biology module integrated with Social-Emotional Learning (SEL) using the ADDIE model and quasi-experimental pretest-posttest control group design at a Islamic integrated senior high school, Bogor (N=63: control n=36, experimental n=27). Instruments included validated questionnaires for digital literacy (DigComp 2.2 framework, Cronbach's α=0.87), creativity (fluency, originality, flexibility, elaboration dimensions, α=0.82), and SEL (SECQ questionnaire, α=0.79; CVR≥0.85). Results showed clear experimental group superiority across all measured variables. Digital literacy achieved high N-Gain of 0.81 (posttest mean=76.73 vs control 66.56; Cohen's d=2.05), creativity recorded moderate-high N-Gain of 0.65 (posttest mean=78.89 vs control 68.92; d=1.27), and SEL showed N-Gain of 0.69 (vs control 0.45; d=0.78), all confirmed significant by ANCOVA (p<0.001). Micro:bit project rubrics further verified creativity improvement, particularly in originality (experimental mean=85 vs control 73.33). The module effectively addresses Indonesia's digital literacy challenges (PISA score=371) while developing essential 21st-century competencies. Integration of STEM-robotics with SEL demonstrates clear superiority over conventional project-based learning, making it highly suitable for implementation within Indonesia's Kurikulum Merdeka framework across high schools nationwide.